EFEKTIFITAS TANAMAN HYDRILLA VERTICILLATA, RUMPUT GAJAH, ECENG GONDOK DALAM PEMBUATAN BIOGAS DENGAN BAHAN DASAR KOTORAN SAPI - Nadia Agustina Irianto; Mohammad Mirwan (EnviroUS, 2021)
Biogas is a flammable gas produced from the fermentation process of organic materials by anaerobic bacteria. These compounds in the digester will be converted into methane compounds which can be burned as an energy source. These materials are cow dung, hydrilla verticillata plants, water hyacinth plants, and elephant grass plants. In this research, we try to use combination materials between cow manure with variations of the three plants with a ratio of 2: 1 and a combination of plant variations with a ratio of 1: 1. To compare the 3 plants which produce biogas optimally. The parameters analyzed consisted of water content, C / N ratio, temperature, pressure, flame duration and methane gas content. The results showed that the best biogas was obtained during fermentation for 30 days in a mixture of cow dung and hydrilla verticillata at a ratio of 2: 1 with a moisture content of 41.3%, a C / N ratio of 21.5%, 50.4%. methane gas levels. And marked by an increase in temperature reaching 35oC also with the longest flame, which is for 72 seconds using a portable stove